Investigating Mathematical Knowledge of Teaching for Secondary Preservice Teachers in Papua New Guinea - Olowa, Murray (SEAMEO Regional Centre for QITEP in Mathematics, 2023)
This article examines the studies investigating the teacher’s mathematics knowledge of teaching by secondary preservice teachers in Papua New Guinea. Previous research on Mathematics Knowledge for Teaching provided support for the study. This study was conducted in recognition of the ongoing problems with Papua New Guinea's curriculum, particularly the teaching of science and mathematics, which have led to a drop in students' performance in these subjects. Subject Matter Knowledge (SMK) and Pedagogical Content Knowledge (PCK) are the two main domains that have been identified. These domains are further subdivided into Knowledge of Content and Students (KCS), Knowledge of Content and Teaching (KCT), and Knowledge of Content and Curriculum (KCC), respectively. Other subdivided areas include Common Content Knowledge (CCK), Specialized Content Knowledge (SCK), and Horizon Content Knowledge (HCK). To determine the relationship between SMK and PCK, research questionnaires were utilized as instruments that could accommodate the various areas of SMK and PCK. Given that the P-value is 0.22>0.05, the study's findings indicate a marginally significant difference in SMK between years one and four. However, since the P-value was 0.007<0.05, it was discovered that year fours have higher PCK than year one. Ultimately, the study has demonstrated that fourth years have higher MKT than first years. The diligent work of final-yearpreservice teachers in mathematics is what caused this difference. It is advised that the mathematics curricula in teacher colleges be reviewed following the findings and expanded to include material on SMK and PCK. The Secondary Teachers College Program Specification Document must include both what and how to teach mathematics.